Causes and Consequences of the Spanish Economic Crisis: Why the Recovery is Taken so Long? - Carballo-Cruz, Francisco (Panoeconomicus, 2011)
Spain is currently facing its worst crisis in the last fifty years. The crisis began as an extension of the international financial crisis, but the internal imbalances accumulated in the pre-crisis period aggravated the situation. At present their incomplete adjustment is making difficult the economic recovery. This paper describes the evolution of the economic crisis in Spain. The real estate sector and the banking sector are analysed in detail, as they played a key role in the detonation and the deepening of the crisis. The results of the main reforms carried out so far are also carefully examined. It also discusses the main factors that have delayed the economic recovery up to now (unemployment and indebtedness), and present some alternatives to define an exit strategy. Key words: Crisis, Real estate, Banking, Debt problems, Unemployment, Public debt. JEL: E24, F34, G21, H63, R31.